HUBUNGAN STATUS GIZI, STATUS KESEHATAN DAN AKTIVITAS FISIK DENGAN KEBUGARAN JASMANI ATLET BULUTANGKIS JAYA RAYA JAKARTA - - Ismanto; Ahmad Sulaeman; Hadi Riyadi (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2012)
Badminton has been the most popular and preferred game in Indonesia. Indonesia has been participating many world class events and even become the winner several times. However, Indonesia’s athlete  performance  for the last ten years were not satisped and it needs improvement considering un-intensive physical exercise, mental orientation, appropriate coaching method, adequate training facilities and optimal nutrition. The aims of thiswas study  to determine the relation betweennutrional and health status, including the physical and fittness condition of Jaya Raya Jakarta Badminton athletes. The study was carried out is in Jaya Raya Jakarta,appliying  cross-sectional study. The samples were taken purposively from  18 athletes at the age of 17, and the collected data were subsequently edited, arranged in a master table according to the scale, units and norms of the size of each data. The figures are calculated according to the formulas that can apply and convert the list of used references. The data was analyzed using the MS-Excel, SPSS 16.0 and Minitab. The average intakes of energy and nutrients for male Jaya Raya Badminton athletes were about 2931 kcal, 67 grams of protein, 105 grams of fat, 417 grams of carbohydrate and 17 milligrams of iron and women athletes were about 2650 kcal, 64 grams of protein, 93 grams of fat, 389 grams of carbohydrate and 15 milligrams of iron.Based on the level of adequacy, the male athletes are still lack of carbohydrates whereas the female ones are lack of carbohydrates and iron. The average nutritional status of Jaya Raya Badminton Athletes is normally at 21.57 ± 2.27 and most of them are generally in good condition. The athletes 94% show activity metabolic (KM) 2.09. Average scores of physical fitness level  (VO2 max) of male athlete is about 49.8 ± 4.6 ml /kg /minute (sufficient) and the female was 41.4 ± 5.6 ml / kg / min (sufficient). The variable related to the level of physical fitness includes nutritional status  (p 0.01) and physical activity (p 0.01), in which the variations in physical fitness score of 92.4% is determined by nutritional status and physical activities. Keywords : Nutritional Status, Physical Fitness, Jaya Raya.